Photocrosslinking O‐GlcNAcylated Proteins to Neighboring Biomolecules. Issue 7 (20th July 2021) - Capota, Emanuela; Wu, Han; Kohler, Jennifer J.
Abstract: This protocol enables identification of the interaction partners of O‐GlcNAcylated proteins. The method involves the introduction of the diazirine photocrosslinker onto the O‐GlcNAc modification within living cells. The photocrosslinker is activated by UV light to yield covalent crosslinking between O‐GlcNAcylated proteins and neighboring molecules. The binding partners can be further characterized by immunoblot or proteomics mass spectrometry methods. The benefits of using the photocrosslinker include the capacity to trap low‐affinity binding interactions and the ability to selectively target the interaction partners of the O‐GlcNAcylated form of the protein of interest. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : In‐cell production and crosslinking of O‐GlcNDAzylated proteins Basic Protocol 2 : Immunoblot analysis to assess O‐GlcNDAz crosslinking Support Protocol : Detection of UDP‐GlcNDAz from cell lysates